2016
DOI: 10.1016/j.bbi.2016.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Chronic peripheral inflammation, hippocampal neurogenesis, and behavior

Abstract: Adult hippocampal neurogenesis is involved in memory and learning, and disrupted neurogenesis is implicated in cognitive impairment and mood disorders, including anxiety and depression. Some long-term peripheral illnesses and metabolic disorders, as well as normal aging, create a state of chronic peripheral inflammation. These conditions are associated with behavioral disturbances linked to disrupted adult hippocampal neurogenesis, such as cognitive impairment, deficits in learning and memory, and depression a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
130
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 213 publications
(147 citation statements)
references
References 102 publications
(144 reference statements)
8
130
1
1
Order By: Relevance
“…We observed impaired adult hippocampal neurogenesis and hippocampal function in the offspring of fructose‐fed dams. Previous studies have demonstrated that neurogenesis is negatively regulated by inflammation and apoptosis (23, 24); however, in the present study, attenuated levels of neurogenesis did not seem to occur as a result of the influence of cytokines or apoptosis. Therefore, the observed decreases in hippocampal function may have been a result of decreases in neurogenesis.…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…We observed impaired adult hippocampal neurogenesis and hippocampal function in the offspring of fructose‐fed dams. Previous studies have demonstrated that neurogenesis is negatively regulated by inflammation and apoptosis (23, 24); however, in the present study, attenuated levels of neurogenesis did not seem to occur as a result of the influence of cytokines or apoptosis. Therefore, the observed decreases in hippocampal function may have been a result of decreases in neurogenesis.…”
Section: Discussioncontrasting
confidence: 95%
“…Research has demonstrated that exposure to adversity in early life-specifically, environmental stress, under-or malnutrition, and infection-leads to lifelong alterations in hippocampal-related cognitive functions, at least in part via changes in hippocampal neurogenesis (22). Such decreases in hippocampal neurogenesis may be explained by several processes, including inflammation, apoptosis, and reduced levels of neurotrophic factors (23)(24)(25).…”
mentioning
confidence: 99%
“…However, children who survived sepsis-associated encephalopathy perform less well after than they did previously (Kaur et al, 2016), Prolonged neonatal medical treatment, especially with mechanical ventilation, which appears to increase the risk of systemic inflammation (Bose et al, 2013), has been associated with specific impairments in mathematic tasks (Jaekel et al, 2014). Also, studies that provoked inflammation in adult rodents (Rogers, 1995;Chesnokova et al, 2016;Ryan and Nolan, 2016), and reports about adults with systemic inflammation (Hong and Banks, 2015;Wardill et al, 2016) support the view that concurrent or very recent inflammation impairs learning (Donzis and Tronson, 2014).…”
Section: What Others Found How Our Findings Are Similar or Differentmentioning
confidence: 97%
“…Brains were rapidly removed, and hippocampi were microdissected and frozen at −80°C until used. The hippocampus was chosen because of its demonstrated roles in affective behavior [24] and memory [25]. Brain tissue was homogenized in TRIzol and then pelleted.…”
Section: Methodsmentioning
confidence: 99%